Multi-channel search for squarks and gluinos in root s=7 TeV pp collisions with the ATLAS detector at the LHC - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
A search for supersymmetric particles in final states with zero, one, and two leptons, with and without jets identified as originating from b-quarks, in 4. 7 fb-1 of √s = 7 TeV pp collisions produced by the Large Hadron Collider and recorded by the ATLAS detector is presented. The search uses a set of variables carrying information on the event kinematics transverse and parallel to the beam line that are sensitive to several topologies expected in supersymmetry. Mutually exclusive final states are defined, allowing a combination of all channels to increase the search sensitivity. No deviation from the Standard Model expectation is observed. Upper limits at 95 % confidence level on visible cross-sections for the production of new particles are extracted. Results are interpreted in the context of the constrained minimal supersymmetric extension to the Standard Model and in supersymmetry-inspired models with diverse, high-multiplicity final states. © 2013 CERN for the benefit of the ATLAS collaboration.